Respon Lima Kultivar Kentang (Solanum tuberosum L.) Terhadap Perlakuan Manitol pada Kultur In Vitro ( - Winna Firdawati; Farida Damayanti; Suseno Amien; Warid Ali Qosim (Zuriat, 2019)
Potato is one of the vegetable commodities that potentially use as a source of carbohydrate and could be developed to support food diversification program. Global climate changes that lead to extreme climate change could cause some agricultural problem, i.e., drought stress. It is necessary to develop drought-tolerant cultivar as one of the options to solve the problem. The objective of this research was to identify the level of drought stress in five potato cultivars by observing the response of those cultivars to mannitol in vitro culture. The experiment was conducted at Tissue Culture Plant Breeding Laboratory, Faculty of Agriculture, Universitas Padjadjaran, on May 2014 to June 2014. The experiment was arranged in a factorial, completely randomized block design with two factors. The first factor was potato cultivar (five levels), consisted of Granola, Atlantik, Andina, Ping 06, and Merbabu 17. The second factor was mannitol concentration (five levels), comprised of 0.0 M, 0.1 M; 0.2 M; 0.3 M, and 0.4 M. The results showed that there was no interaction between potato cultivar and mannitol concentration in all traits. Number of leaves, number of nodes, number of roots, root length were independently affected by cultivar and mannitol concentration, meanwhile plantlet height, chlorophyll concentration was only individuals affected by mannitol concentration. It was also showed that mannitol concentration of 0.4 M decreased plantlets height, a number of leaves, and a number of roots in potato cultivars Granola, Atlantik, Andina, Ping 06 dan Merbabu 17.